1978
DOI: 10.1083/jcb.76.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular divalent cation release in pancreatic acinar cells during stimulus-secretion coupling. I. Use of chlorotetracycline as fluorescent probe.

Abstract: Stimulus-secretion coupling in pancreatic exocrine cells was studied using dissociated acini, prepared from mouse pancreas, and chlorotetracycline (CTC), a fluorescent probe which forms highly fluorescent complexes with Ca ~+ and Mg ~+ ions bound to membranes. Acini, preloaded by incubation with CTC (100/xM), displayed a fluorescence having spectral properties like that of CTC complexed to calcium (excitation and emission maxima at 398 and 527 nm, respectively). Stimulation with either bethanechol or caerulein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 36 publications
5
46
0
1
Order By: Relevance
“…Although other factors could have affected ieared to mobilize Ca2+ only from a pool (or CTC fluorescence, the very close parallels betweeni was monitored completely by incubating the effects of TRH on 45Ca2+ efflux and CTC fluoreswith 100 ,M CTC for 10 min. This con-cence suggest that the decrease in fluorescence caused s based on1 the finding that TRH caused a by TRH is best explained by displacement of memolute decrease in CTC fluorescence irre-brane-bound Ca2+, as has been concluded for other the duration of incubation with CTC be-secretagogues (28)(29)(30)(31)(32)(33)(34)(35). nd 120 mim, even though the total fluoresIt has been suggested that stimulation of release of isity increased with longer inctubations (data adenohypophyseal hormones may be dependent on Hence, it seems likely that TRH mobilized extracellular Ca2+ (36,37).…”
Section: Methodsmentioning
confidence: 66%
“…Although other factors could have affected ieared to mobilize Ca2+ only from a pool (or CTC fluorescence, the very close parallels betweeni was monitored completely by incubating the effects of TRH on 45Ca2+ efflux and CTC fluoreswith 100 ,M CTC for 10 min. This con-cence suggest that the decrease in fluorescence caused s based on1 the finding that TRH caused a by TRH is best explained by displacement of memolute decrease in CTC fluorescence irre-brane-bound Ca2+, as has been concluded for other the duration of incubation with CTC be-secretagogues (28)(29)(30)(31)(32)(33)(34)(35). nd 120 mim, even though the total fluoresIt has been suggested that stimulation of release of isity increased with longer inctubations (data adenohypophyseal hormones may be dependent on Hence, it seems likely that TRH mobilized extracellular Ca2+ (36,37).…”
Section: Methodsmentioning
confidence: 66%
“…We chose 50 AM CTC as a standard concentration for all subsequent studies. In previous studies with other organelles and cells, the CTC concentration used to measure membrane-associated Mg" and Ca>2 has varied from 10 ,M (4,24) up to 100 ,uM (6,23).…”
Section: Mg2+ Effects On Ctc Fluorescencementioning
confidence: 99%
“…The fluorescence emission of CTC2 has been used to measure the level of divalent cations (specifically Mg2" and Ca2") associated with envelope membranes in a wide range of animal cells and subcellular particles such as erythrocytes (23), pancreatic acinar (6) and islet (24) cells, brain synaptosomes (3), liver mitochondria (4, 16), and sarcoplasmic reticulum vesicles from skeletal muscle (18). The quantum yield of the complex increases in apolar, in comparison to aqueous environments (16).…”
mentioning
confidence: 99%
“…We examined whether the two fluorescent probes competed with each other for the DNA strand structure. CTC chelates Mg2+ as well as Ca2+ and both chelate compounds caused a spectral shift of the fluorescent emission of CTC (2,3,12). From the spectra of EB and CTC, we found that the emissions could be recorded separately by measuring F590 excited at 510 nm for EB, F520 excited at 400 nm for CTC-Mg and F420 excited at 350 nm for CTC alone, although there was some spectral overlapping of these spectra.…”
Section: Discussionmentioning
confidence: 85%